2007
DOI: 10.12968/jowc.2007.16.9.27866
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and acceptability of a new two-layer bandage system for venous leg ulcers

Abstract: This new two-bandage compression system is effective and well accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 25 publications
1
40
1
4
Order By: Relevance
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 90%
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 90%
“…7 Patients affected with venous ulcers experience a decrease in their overall health-related quality of life, including severe pain, impaired mobility, limited work capacity and negative emotions. 8,9 Risk factors for venous disease include family history of venous disease or inherited coagulopathy, employment with requirements for prolonged standing, smoking, obesity, hypertension and/or leg trauma. 5 Treatment of venous ulcers varies from multiple surgical procedures to the use of various topical agents combined with external pressure support to the legs.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,10 Even with good compression therapy, approximately 40-50% of ulcers do not achieve complete closure within 6 months of therapy. 4,8,9 Because of this low healing rate and a recidivism rate of nearly 70%, multiple wound-healing agents, cytokine growth factors and cell-based devices have been used to determine if closure of venous ulcers can be facilitated without operative intervention. 1,[8][9][10][11] Topical compression therapy provides a means to treat or prevent adverse effects as noted above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the healing rates reported for VLU vary considerably. [9][10][11][12][13][14][15][16][17][18][19] Technical solutions to variability in application of bandages include printed ovals or rectangles that change to circles or squares at the correct bandage extension; markings on orthostatic devices that are matched to a scale; bandage application at full stretch. Direct measurement of interface pressure may be used on application and for monitoring 20 but pressure is usually measured at only one anatomic location.…”
Section: Introductionmentioning
confidence: 99%